2020
DOI: 10.3390/su12219218
|View full text |Cite
|
Sign up to set email alerts
|

Salinity Stress Mitigation Using Encapsulated Biofertilizers for Sustainable Agriculture

Abstract: The harmful effect of salinity stress on crops needs to be mitigated. Therefore, the application of microbial inoculum in combination with nanomaterials and methyl salicylate was investigated. Initially, different seeds were exposed to salinity levels treated with variable microbial treatments using different modes of applications. The microbial treatments included application of cyanobacterial strain Cyanothece sp. and the rhizobacterium Enterobacter cloacae, alone or in combination with one another, and a fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Another study on soil salinity showed that cyanobacteria Cyanothece sp. and Rhizobacter enterobacter cloacae were encapsulated with methyl salicylate [119]. In addition, various nanomaterials such as graphene, graphene oxide, and carbon nanotubes were used in combination with biofertilizers against soil salinity in encapsulated form.…”
Section: Bacterial Encapsulation With Various Polymers Against Salinity Stressmentioning
confidence: 99%
See 2 more Smart Citations
“…Another study on soil salinity showed that cyanobacteria Cyanothece sp. and Rhizobacter enterobacter cloacae were encapsulated with methyl salicylate [119]. In addition, various nanomaterials such as graphene, graphene oxide, and carbon nanotubes were used in combination with biofertilizers against soil salinity in encapsulated form.…”
Section: Bacterial Encapsulation With Various Polymers Against Salinity Stressmentioning
confidence: 99%
“…The bacteria tested included the cyanobacterial strain Cyanothece sp. and the rhizobacterium Enterobacter cloacae, which was applied to wheat in the field [119]. The results showed that this encapsulation reduced the destructive effect of salinity stress, especially when combined with methyl salicylate.…”
Section: Examples Of Using Pgpr Encapsulation Against Salinity Stress In Different Plantsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Semary et al (2020) different microbial treatment, mechanisms can reduce salinity stress. Recent studies have revealed that halotolerant rhizobacterials are able to reduce salinity stress by increasing root surface area through the regulation of phytohormones and gene expression when auxin increases and abscisic acid decreases.…”
Section: Resultsmentioning
confidence: 99%
“…is a nitrogen-fixing unicellular cyanobacterium that is capable of performing photosynthesis and nitrogen fixation in a diurnal cycle controlled by circadian rhythm. Many reports demonstrated its fantastic metabolic activities and physiological attributes including gold nanoparticle biosynthesis and plant biofertilization (Younis et al, 2019;El Semary et al, 2020). In order to exploit this cyanobacterium further and to grow it at minimal cost, we tested two natural different carbon sources including dextrose (glucose) derived from corn and soil extract as carbon sources.…”
Section: Introductionmentioning
confidence: 99%